Генетико-математичний аналіз вмісту жиру в молоці корів і виходу молочного жиру за структурою стада чорно-рябої породи - Маменко, О.М.; Ємець, З.В. (Фактори експериментальної еволюції організмів, 2016)
Aim. The «genetic group» was used as one of the genetic factors and as a result the genetic and mathematical analysis of fat content in cow’s milk and the output of milk fat depending on the origin of genetic groups in the structure of blackand-white breed on the farms, mainly in Kharkiv region has been carried out. Methods. The hybrids /mongrels/ produced by the scheme of back crossing (BM3/4+H1/4) were characterized by the highest variability by the content of fat in cow’s milk and the lowest level was in the hybrids produced by the scheme – BM1/2+HO1/4+HO1/4 (ơ = 0.177%). Results. Among the hybrids on the basis of the Black-and-Motley breed the cows of the genotype BM1/2+H1/4+HO1/4 (ơ = 59.4224 kg) were characterized by the highest output of milk fat, the lowest value was in the hybrids BM1/4+H3/4 (ơ = 44.97 kg).Thus, in the latter group the above productive parameter is the most constant at the lowest mean content of milk fat. The degree of the effect of the genetic group on the content of fat in cow’s milk was η₂ = 0,003. The degree of the effect of the genetic group on the output of milk fat was η₂ = 0,031. Conclusions. To estimate the most probable values of fat content in cow’s milk and the output of milk fat it is expedient to use the stipulating factors «genetic group», «genetic group – year of birth», «genetic group – year of calving», «genetic group – father».